Experience in treating patients with a combination of the descending aorta saccular aneurysm and spondylodiscitis - M.D. Tonchev (NAMS of Ukraine, State Organization "Scientific-Practical Center of Endovascular Neuroradiology, Non-Governmental Organization “All Ukrainian Association of Endovascular Neuroradiology, Shupyk National Healthcare University of Ukraine, 2021)
The article presents a clinical case of treatment of a patient with spondylodiscitis of two levels – thoracic and lumbar spine spondylodiscitis combined with the thoracic aorta aneurysm. A 68-year-old patient was hospitalized in the Neurosurgical Department of the M.V. Sklifosovsky Poltava Regional Clinical Hospital in August 2019 with complaints of pain and discomfort in the thoracic and lumbar spine, shoulder joints, severe weakness in the lower extremities. The multislice computed tomography with intravenous contrast revealed a sac-like aneurysm of the descending thoracic aorta at the level of vertebrae Th4-Th5 with invasion into the vertebral bodies, spondylodiscitis of vertebrae Th4-Th5 and Th11-Th12 with deformation of the spinal axis, the formation of absolute stenosis of the spinal canal at the level of vertebrae Th11-Th12. At the first stage of the surgery, the thoracic aortic arthroplasty was performed using TAA Stent Graft System (Ankura, China) 34 × 34 × 160 mm at the M.M. Amosov National Institute of Cardiovascular Surgery and the exclusion of the descending aorta aneurysm from the bloodstream was maintained. At the second stage, transpedicular stabilization of the spine at the level of vertebrae Th10-Th11-L2-L3 was performed at the M.V. Sklifosovsky Poltava Regional Clinical Hospital using Legacy system (Medtronic, USA) and spinal cord compression was eliminated. The treatment of spondylodiscitis at the level of the vertebrae Th4-Th5 was conservative with the use of osteotropic antibacterial drugs. The patient was mobilized in the early post-surgical period after stabilization of the spine. Regression of pain syndrome and lower paraparesis was noted. Further observation was performed on an outpatient basis. According to the modified Rankin Scale, which allows assessing the degree of independence of the patient in everyday life, the patient was evaluated with 3 points at discharge. A follow-up examination at 3, 12, and 24 months showed that the functioning of the stent-graft and transpedicular system were satisfactory. The result of 0 points according to the modified Rankin Scale. Patients with the thoracic spine spondylodiscitis require special attention and additional diagnostic procedures. The risk of additional combined pathology in the form of thoracic and abdominal aorta aneurysms should be considered when planning surgical treatment.